Implementasi Manajemen Pengetahuan Pada Perusahaan Web Hosting Dengan Web Hosting Management Complete Solution - Angga Pramudianto; Christina Juliane (Infotekmesin, 2022)
The implementation of knowledge management in a company has become a necessity in the current 4.0 era. Therefore, the company's ability to manage existing knowledge is needed to survive the onslaught of competition. To implement knowledge management in one of the Web Hosting companies towards service to consumers is the aim of this research, as well as a solution to the problems experienced in the Customer Support division. Due to this, the problem-solving process is often hampered and the existing problems are not properly archived. In this study, knowledge of the organization is figured out by analyzing the support of existing information technology. Focus Group Discussion (FGD) method is used as a tool to find out the abilities and skills that exist in each of them, in order to figure out the extent to which a person's perspective is to see and assess something he observes. In this study, Web Hosting Management Complete Solution (WHMCS) is a system used in applying knowledge to web hosting companies for the knowledge-sharing process between customer support and consumers.